ANALYSIS AND IMPLEMENTATION OF UBUNTU AND MIKROTIK BASED SERVER - Januardi Nasir (Merdeka Malang University, 2019)
Internet is a primary requirement in this modern era because it is one of the information’s media and communication. Due to its rapid advancement, internet is now a main infrastructure which must be possessed by an organization, institution (education, government, service provider and others). Besides internet, other infrastructure which is also a primary requirement in an institution is a centralized storage or server. Regarding internet’s availability and server, PT Indonesia Terbit Media faces some setbacks such as the unavailability of sufficient bandwidth management and unavailability of centralized information storage. To solve those setbacks, a MikroTik router is offered to be implemented in the company’s network. Before doing research, observation is held in the company to gather information’s regarding current network. Along with observation, focus group discussion is held with the staffs. After information’s are gathered, current network is analyzed then a new topology is proposed. After the proposal is approved, testing phase is initiated to know the contributions of newly proposed network in solving the mentioned setbacks. Results from the implementation are such as bandwidth management is applied in new network which is resulting in stable internet’s speed even though a user is downloading a quite large file and Ubuntu-based centralized server.DOI : https://doi.org/10.26905/jeemecs.v2i1.2928